DANCING, AN AGENT OF DIDACTICS OF THE PERSONALITY OF YOUNG STUDENTS (Fiep Bulletin - online, 2014)
Dance is an outburst for young people’s exteriorization. It represents a communication tool of all types of personality, being used in various specific ways and with the help of different dance styles. The dance character is discovered by the “dance study”. The dancer’s personality is discovered through “dance”, this being added to the reaction and manifestation method, the lifestyle, the cultural, intellectual and spiritual background as well as the expression and performance capacity of the dancer. With the help of dance one can express sadness, exaltation, passion, the entire ensembles of potential states and emotions. Dance represents a boost of the soul, an expression of personality, becoming part of young people’s intense life, shaping the young personality through self-confidence, ease of expression, eliminating inhibition, introversion and fear of extroversion. Dance in day-to-day life is used as a tool of psychical, psychological, social and cultural education, according to everyone’s personality. In order to educate and shape the young people’s personality, dance genres were used in contrast with their character and vital energy, to achieve development of other aspects and natures which are less active. The purpose is to observe their reaction and manifestation when faced with new situations and their focus power in order to overcome the difficulty of the existing circumstances, with the help of a certain behavior and attitude contributing to “personality modeling”. The research aims to contribute to the promotion of dance activity within collectivity as well as in a currently computerized society, by choosing psychological and heterogeneous dance programs for different  personalities and types of teenagers, in order to create communication bridges among them. This determines the track down of most attractive dance methods, finding dances specific to their age and personalities, the purpose set by the organizers of these psycho-artistic activities being to shape young personality as much as possible depending on their nature, for a better integration into society and an efficient result in developing future professional activities and eliminating school stress. The objectives of the research are set to solve these requirements, derived from and requested by practice. The final purpose is the modeling of teenagers’ personality according to their nature, no matter the used methods or type of developed activity.
Keywords: artistic dancing; personality; temperament; rhythm; effort; natural motion; elegance; delicacy